Analysis of Changes in the Status of Waqf Assets to Improve the Quality of Islamic Education in SD Muhammadiyah Innovative Mertoyudan Magelang - Usman, Nurodin; Miswanto, Agus; Nugroho, Irham (Universitas Muhammadiyah Magelang, 2022)
The process of changing the status of waqf in the field of education is one of the investment instruments to improve the performance of Islamic educational institutions. Educational waqf institutions that are not strategic are suspected to be one of the reasons for the undeveloped education. This study analyzes the process of changing the status of waqf assets in the field of education, namely Muhammadiyah Pujotomo Elementary School, through a benefit exchange mechanism with Muhammadiyah University of Magelang. At first, the school was located behind the campus so that the community could not easily access it. After occupying a new location and building, the school's name changed to SD Muhammadiyah Innovative and has experienced significant development. The results of the analysis show that changing the status of waqf land at Innovative Muhammadiyah Elementary School can improve the educational quality of the institution so that it becomes better and has more promising development prospects.